Entering into a Community-University Collaboration: Reflections from Dig Deep Farms - Neideffer, Marty (Journal of Agriculture, Food Systems, and Community Development, 2018)
First paragraphs: We found a way to grow carrots, to look people straight in the eye and say, “That’s good community policing.” It was an unusual process that ultimately led the Alameda County Sheriff’s Office in San Leandro, California to become one of the five community sites across the country participating in the Food Dignity Research project. Signing on to that project opened a new door for us to execute the vision we had for our work in community food production as part of community policing. The most beneficial aspect of it was to be with people who were like-minded and didn’t think we were crazy. In 2009, elements of the Alameda County Sheriff’s Office and the leadership of the Alameda County Deputy Sheriffs’ Activities League, Inc., (a nonprofit corporation established to leverage crime prevention efforts of the sheriff’s office), came to a conclusion: poverty, in all its various aspects, is a root driver of crime. Therefore, to credibly address crime in the poor, underserved communities of Ashland and Cherryland, we had to first address the issue of poverty.... See the <a title="press release archive " href="http://www.icontact-archive.com/archive?c=488966&f=60033&s=84565&m=962913&t=257c360ddc23fcec50d37942ed548ee4169a6c0d76d51e227fa886af9ecdf0c7" target="_blank" rel="noopener">press release for this article.